Three Coccidiocidal Drugs, Three Different Responses Observed in Broiler Chickens Challenged with Eimeria tenella Oocyst - Jamilu, Muhammad Abubakar; Nanjul, Goselle Obed; Amina, Dalhatu; Ngozichukwu, Joachim Blessing; Martha, Habu Bwehafa; Rhoda, Abiola Oluwanifemi; Sunday, Udoh Shedrack; Ejete, Oliseemeka Charles; Idoko, Ojochemi Sunday; Ahmadu, Yahaya Mbaya; Ajiji, Godwin Yandu; Nanvyat, Nannim; et al. (Asian Journal of Biological and Life Sciences)
Background: The successes in the poultry industry are being diminished by ravaging effect of coccidiosis that result in great mortality of birds and economic losses to farmers. Here, we describe the responses of three coccidiocidal drugs commonly used by poultry farmers in tropical regions. Materials and Methods: The weight performance, faecal oocysts count, haematological parameters and histopathological architecture were investigated. Twenty-five days old broiler chickens of both sexes were randomly assigned to five groups. Of these 5 groups, groups 1-4 were orally inoculated with 4x103 (0.2ml) sporulated oocysts of Eimeria tenella as a single gavage, while group 5 (negative control) were administered water. Whereas groups 1-3 were treated with same regime (100%) of drugs, group 4 served as the positive control. Results and Conclusion: The results indicated that inoculated birds had significantly reduced growth rate and varied haematological parameters, but increased faecal oocysts shedding with sloughing, and also had necrosis in the intestine. These parameters were however reversed after nine days of treatment with significant improvement observed in all the treated groups with the highest effects in groups 1 and 2. Statistical analysis showed a significant difference at P< 0.05. In conclusion, we report that the three drugs worked effectively in the boosting of the listed parameters. But importantly, Embazin had best effects on eliminating oocyst in the faeces, while Diclazuril had the most improved effect on the haematological and histological architectures. We therefore propose that a combination of the three synthetic drugs could offer the best result since they could complement the shortfall of each other.
Keywords: Drug regimes; Eimeria tenella; Haematogical parameters; Histological architecture.; Oocysts count; Weight performance